UURDU 1 TWO NUCLEAR STATES PAKISTAN AND INDIA (AN ANALYSIS): پاک بھارت ایٹمی ممالک، تصفیہ طلب مسائل : ایک مطالعہ - Jabeen, Rizwana; Khan, Mamnoon Ahmed (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2021)
Since the time of its inception and India is sharing an elongeted history of conflicting issues which not only constructed an ambiance of scepticism and distrust among there two nations and their respective governments, but at the same time it barricade the scope and possibilities of peaceful solutions of the longstanding, complex issues, such as Kashmir, Indus water distribution, cross border troubles and terrorism, sir creek border issue, line of control (LOC) and siachen. It has been observed through out the course of history that the efforts and the measures to normalize the political stress between India and Pakistan did never bring a rewarding outcome. Therefore the complexity and the murkiness of there undersolved issues has aggravated to the height which set an impression of at most an impossible errand. This article is an attempt to delve into the reasons and the factors behind the failed attempts in the process of conflict resolution between India and Pakistan the historical findings and the political analysis of the data / facts used in this article verify the statement that the hard core policies and an unbending attitude towards the resolutions of Kashmir issue has never been a success idea, instead, in the light of the current political, economics and strategic. Scenario there is a need to resolve the long standing issues on priority as well as need basis. Despite of putting all the workable options on hold the governments policy makes and the influential stake holders from both sides should present something new and more result oriented on the table, this can only be happen if the flanking issues like sir creek, intra state terrorism and water distribution would handle in a productive manner.